2020
DOI: 10.1186/s13046-020-01736-2
|View full text |Cite|
|
Sign up to set email alerts
|

New insights in gene expression alteration as effect of doxorubicin drug resistance in triple negative breast cancer cells

Abstract: Background Triple negative breast cancer (TNBC) is a heterogeneous disease with aggressive behavior and an unfavorable prognosis rate. Due to the lack of surface receptors, TNBC must be intensely investigated in order to establish a suitable treatment for patients with this pathology. Chemoresistance is an important reason for therapeutic failure in TNBC. Method The aim of this study was to investigate the effect of doxorubicin in TNBC cell lines and to highlight cellular and molecular alterations after a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Doxorubicin induces cell death and cell growth arrest primarily by inhibition of the topoisomerase II activity, DNA intercalation and production of free radicals, leading to apoptosis, autophagy, senescence and necrosis of the fast-growing cancer cells (Burgess et al, 2008;Meredith and Dass, 2016). In spite of the numerous genes, non-coding RNA and signaling pathways associated with doxorubicin resistance in breast cancer have been identified (Tormo et al, 2019;Ciocan-Cartita et al, 2020;Tanaka et al, 2020), the epigenetic regulatory mechanism, especially the role of chromatin-mediated processes in the regulation of gene expression, has not been investigated yet. Therefore, exploring the regulatory elements of doxorubicin-resistant genes and their corresponding transcription factors (TFs) in breast cancer is critically important for the elucidation of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin induces cell death and cell growth arrest primarily by inhibition of the topoisomerase II activity, DNA intercalation and production of free radicals, leading to apoptosis, autophagy, senescence and necrosis of the fast-growing cancer cells (Burgess et al, 2008;Meredith and Dass, 2016). In spite of the numerous genes, non-coding RNA and signaling pathways associated with doxorubicin resistance in breast cancer have been identified (Tormo et al, 2019;Ciocan-Cartita et al, 2020;Tanaka et al, 2020), the epigenetic regulatory mechanism, especially the role of chromatin-mediated processes in the regulation of gene expression, has not been investigated yet. Therefore, exploring the regulatory elements of doxorubicin-resistant genes and their corresponding transcription factors (TFs) in breast cancer is critically important for the elucidation of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…6 . In addition, we aimed to compared the transcriptomic signature obtained with our compounds with previously published in relation to resistance to chemotherapy, as performed by other groups [ 22 ]. A gene drug resistance signature (NCBI, Accession: GPL1124) was compared with the down- and upregulated transcripts that we obtained after the administration of the different treatments (FC < -2, FC > 2, Supp.Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DQ601914.1). We compiled a list of genes (CYP1A1, CYP1A2, ABCB1, GSTP1, MVP, EPHX1) 13 , RRM1 68 , RRM2 35 , (ABCC3, ABCC6, JUNB, CLU) 69 , (TOP2A, MCM4) 70 from previous studies on DOX resistance reported in different cancers such as breast cancer 13,69 , adrenocortical cancer 68 , pancreatic cancer 35 , and gastric cancer 70 . The complete mRNA sequence of these genes was retrieved from NCBI.…”
Section: Methodsmentioning
confidence: 99%